Effects of process, operational and environmental variables on biohydrogen production using palm oil mill effluent (POME) - Zainal, Bidattul Syirat; Zinatizadeh, Ali Akhbar; Ong, Hwai Chyuan; Mohd, Nuruol Syuhadaa; Ibrahim, Shaliza (Elsevier, 2018)
A batch study for biohydrogen production was conducted using raw palm oil mill effluent (POME) and POME sludge as a feed and inoculum respectively. Response Surface Methodology (RSM) was used to design the experiments. Experiments were conducted at different reaction temperatures (30–50 °C), inoculum size to substrate ratios (I:S) and reaction times (8–24 h). An optimum condition of biohydrogen production was achieved with COD removal efficiency of 21.95% with hydrogen yield of 28.47 ml H2 g−1 COD removed. The I:S ratio was 40:60, with reaction temperature of 50 °C at 8 h of reaction time. The study showed that a lower substrate concentration (less than 20 g L−1) for biohydrogen production using pre-settled POME was achievable, with optimum HRT of 8 h under thermophilic condition (50 °C). This study also found that pre-settled POME is feasible to be used as a substrate for biohydrogen production under thermophilic condition.